IMPROVING THE REMOTE CLIMATE CONTROL SYSTEM BASED ON SOLAR COLLECTORS - Abdiyev Hasan Ergash son (Galaxy International Interdisciplinary Research Journal, 2021)
Experiments have shown that the new controller required in practice the function of automatic storage of the CDcard module, both in the laboratory and in industry and the economy. Another project parameter is the remote control system, which we used to exchange data via the simplest mobile Bluetooth module. This solution is the first step in remote control technology. In the future, the extension of the distance opened a wide way to further improve management control.